Management control systems and performance: evidence from Malaysian local authorities / Norazlina Ilias - Ilias, Norazlina (Institute of Graduate Studies, UiTM, 2016)
The purpose of this study was to investigate the structural relationship between organizational culture, management control systems (MCSs) and the performance of Malaysian local authorities. This study was motivated by the inconsistent findings concerning the relationship between the control system and performance that appeared in the current literature, as well as the personal observations of the researcher. Due to the inconsistencies in the findings, several studies suggest that future researchers investigate MCSs as a tool to improve the performance of organizations. Therefore, this study integrated the organizational culture and MCSs literature by investigating the control systems variable, as control systems have been widely discussed in management accounting literature as an important variable for the purpose of achieving organizational objectives. In this study, three dimensions of MCSs have been identified: external control, internal formal control, and internal informal control. The performance of the local authorities under study was measured using three dimensions of performance: financial, service quality, and procedural. A questionnaire-based survey was carried out to seek responses from 449 departments attached to the local authorities within Peninsular Malaysia. Out of the 449 questionnaires distributed, 367 were returned, which resulted in 335 usable responses that were used for further analysis. This study performed two phases of data analyses: preliminary analysis and structural equation modeling (SEM) analysis…